Pengaruh Pola Konsumsi Anak Sekolah Dasar Terhadap Status Gizi (IMT/U) di Desa Oeltua Kecamtan Taibenu Kabupaten Kupang - Yohanes Don Bosko Demu; Santa Luciana Diaz Vera da Costa; Regina Maria Boro (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The role of parents is very important in preparing nutritious food so that it can improve the nutritional status and health of school children. This research aims to determine food consumption patterns on nutritional status (BMI/U) in elementary school children in Oeltua village, Taibenu subdistrict, Kupang regency. The research design used cross-sectional. The sample used in this research was 206 respondents selected using total sampling. Next, the data was analyzed using the T test. The results of the study showed that there was no influence of energy, fat, carbohydrate intake on the nutritional status (BMI/U) of students (sign=0.998, 0.715, 0.999), there was an influence of protein intake, diet on nutritional status (BMI/U) (Sign = 0.016, 0.018) elementary school children in Oeltua Village. It is recommended that parents play a more adequate role in providing food to their children so that they can improve their nutritional status. There needs to be cooperation between parents and teachers in providing education about the importance of consuming nutritious food.